The attitudes and motivations towards learning English as a foreign language among Chinese students in Shaanxi province, China - Zhang, Hui; Mohamed Razali, Abu Bakar (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This paper aims to propose a study to analyze different kinds of attitudes and motivations towards learning English as a foreign language; to study how the attitudes and motivations influence English learning; and to learn about the relationship between attitudes, motivations and English learning among Chinese students in China. From the literature review, Chinese students, including Hong Kong students, are not willing to communicate with others in English. They are used to learning in the classroom and listening silently to teachers due to the traditional Chinese culture. As such, their communicative practices are not really well-developed. This issue has been reported to have stemmed from lacking motivation to use the English language. According to Wong (2007), there are four basic kinds of motivations which influence English learning: Intrinsic Motivation, Extrinsic Motivation, Integrative Motivation and Instrumental Motivation. In this proposal the researchers proposes to study 60 participants from two high schools in Xi’an City Shaanxi Province China who will be required to complete the questionnaires. Among them, 30 students will be selected randomly to be interviewed respectively. Through investigating of both questionnaire and interview, we hope to learn if attitudes and motivations indeed have the effect on English learning for Chinese students; secondly, if the active and positive attitudes and motivations improve their English learning; thirdly, if out-of-school activities should be increased to enhance Chinese students’ attitudes and motivations to learn English; fourthly, if the four basic motivations play important roles on the English performance in Chinese students; lastly, if some other factors, such as self-esteem, anxiety, risk-taking, nervousness and shyness can also lead to avoidance to learning English among Chinese students.